Pengaruh Kandungan Pati Singkong Terpregelatinasi Terhadap Karakteristik Fisik Tablet Lepas Terkontrol Teofilin - Juheini, Juheini; Iskandarsyah, Iskandarsyah; J.A, Animar; Jenny, Jenny (Majalah Ilmu Kefarmasian, 2004)
In order to make use of pregelatinized Manihot starch in controlled release tablet, the research was done by heating the starch suspension up to its gelatinized temperatur, then dried. The particle size of pregelatinized Manihot starch used were (100-150 mesh) : (150-250 mesh) : smaller than 200 mesh = 3,5 : 1 : 1. The effect of pregelatinized Manihot starch on physical characteristic of Theophyllin controlled relase tablet was known by using 4 formulas containing variety of pregelatinized starch as follows: 30%, 40%, 50%, and 60%. Evaluation on the tablet results including tablet mass and size uniformity, hardness and friability. The result showed that pregelatinized Manihot starch in variable content on these tablet formulas fulfilled the requirement of tablet physical characteristics.